Baddeleyite in pneumatholytic aureoles above the sulfide droplets in picrate gabbrodolerites, plagiolherzolites and troctolites of ore intrusives of Norilsk type - A. A. Serova; E. M. Spiridonov (Известия высших учебных заведений: Геология и разведка, 2015)
Baddeleyite has been found in disseminated sulfide ores of the Noril’sk ore field within the pneumatholytic aureoles presented above the sulfide droplets. The baddeleyite occurs as lamellae within ilmenite crystals. It contains «1 wt.% HfO2. This new occurrence of baddeleyite and the pneumatholytic aureole mineral assemblage indicates that fluids exsolved from highly fractionated sulfide meltswere enriched in К, P, Ti, but also contained Zr, REE and Cl, F, H2O, SO3. The mineral assemblage of the pneumatholytic aureoles is estimated to form at temperatures around 780-820°С based on the titanomagnetite-ilmenite geothermometry.